ACE! How the Waste Management Phoenix Open Rose from the Ash Heap to become a Sponsorship Exemplar - Lee P McGinnis; Keevan Statz (Journal of Applied Sports Management, 2023)
Waste Management leverages the PGA TOUR’s so-called “People’s Open” in a manner that is unparalleled in the sport industry. The Waste Management Phoenix Open (WMPO) is not only a zero-waste event but also utilizes activation tactics that maximize this value proposition for consumers through sponsored activities that engage fans of all ages, backgrounds, and motivations. After an extensive analysis of the event and what makes it distinct, we propose a framework that we term ACE (Activation optimization, Cohesive value propositions, and Experientially focused programs), which can serve as a three-pronged test that event/property owners and sponsors alike can use to achieve desired results.
Keywords: sponsorship; event management; servicescape; fit; incongruence; activation